Tindak Tutur Direktif Guru dalam Proses Belajar Mengajar di TK Nusa Indah Banuaran Padang - Elmita, Winda; Ermanto, Ermanto; Ratna, Ellya (Universitas Negeri Padang, 2013)
This article was wrote to (1) describle the form of directive speech act that was used by the teacher in teaching and learning process, (2) describle strategy of speech act of teacher in teaching and learning process at Nusa Indah kindergarten. The data of this study were directive speech act of teacher kindergarten. The primary source of data were speech act of teacher at Nusa Indah kindergarten. Data were collected by using observation methods and record technique and note taking as an advanced technique. The findings of the study showed that there are five form of directive speech act, which was command, appeal, suggest, advise and defy. Two strategy of speech act are the admittedly without platitude of speech act and the admittedly by platitude in positive manners of speech act.